Shakespeare in Chinese Cinema - Hui Wu (Multicultural Shakespeare, 2013)
Shakespeare’s plays were first adapted in the Chinese cinema in the era of silent motion pictures, such as A Woman Lawyer (from The Merchant of Venice, 1927), and A Spray of Plum Blossoms (from The Two Gentlemen of Verona, 1931). The most recent Chinese adaptations/spinoffs include two 2006 films based on Hamlet. After a brief review of Shakespeare’s history in the Chinese cinema, this study compares the two Chinese Hamlets released in 2006—Feng Xiaogang’s Banquet and Hu Xuehua’s Prince of the Himalayas to illustrate how Chinese filmmakers approach Shakespeare. Both re-invent Shakespeare’s Hamlet story and transfer it to a specific time, culture and landscape. The story of The Banquet takes place in a warring state in China of the 10th century while The Prince is set in pre-Buddhist Tibet. The former as a blockbuster movie in China has gained a financial success albeit being criticised for its commercial aesthetics. The latter, on the other hand, has raised attention amongst academics and critics and won several prizes though not as successful on the movie market. This study examines how the two Chinese Hamlet movies treat Shakespeare’s story in using different filmic strategies of story, character, picture, music and style.